Implementing evidence-informed policy into practice for health care professionals managing people with low back pain in Australian rural settings: A preliminary prospective single-cohort study - Slater, Helen; Briggs, Andrew; Smith, Anne; Bunzli, Samantha; Davies, Stephanie; Quintner, J. (Wiley-Blackwell Publishing, Inc, 2014)
Objective: To provide access to professional development opportunities for health care professionals, especially in rural Australian regions, consistent with recommendations in the Australian National Pain Strategy and state government policy. Design and Setting: A preliminary prospective, single-cohort study design, which aligned health policy with evidence-informed clinical practice, evaluated the implementation and effectiveness of an interprofessional, health care provider pain education program (hPEP) for management of nonspecific low back pain (nsLBP) in rural Western Australia. Intervention: The 6.5-hour hPEP intervention was delivered to 60 care providers (caseload nsLBP 19.8% ± 22.5) at four rural WA regions. Outcome Measures: Outcomes were recorded at baseline and 2 months post-intervention regarding attitudes, beliefs (modified Health Care Providers Pain and Impairment Relationship Scale [HC-PAIRS]), Back Pain Beliefs Questionnaire [BBQ]), and self-reported evidence-based clinical practice (knowledge and skills regarding nsLBP, rated on a 5-point Likert scale with 1 = nil and 5 = excellent).Results: hPEP was feasible to implement. At 2 months post-hPEP, responders' (response rate 53%) improved evidence-based beliefs were indicated by HC-PAIRS scores: baseline mean (SD) [43.2 (9.3)]; mean difference (95% CI) [−5.9 (−8.6 to −3.1)]; and BBQ baseline [34.3 (6.8)]; mean difference [2.1 (0.5 to 3.6)]. Positive shifts were observed for all measures of clinical knowledge and skills (P < 0.001) and increased assistance with planning lifestyle changes (P < 0.001), advice on self-management (P = 0.010), and for decreased referrals for spinal imaging (P = 0.03). Conclusions: This policy-into-practice educational program is feasible to implement in rural Western Australia (WA). While preliminary data are encouraging, a further randomized controlled trial is recommended.